Episiotomy Approach in Management of Dystocia Due to Vulval Stenosis in A Crossbred Jersey Heifer - Raja, S.; Prabaharan, V.; Prakash, S.; Satheshkumar, S.; Alagar, S.; Zahangina , K.R. A. (The Indian Journal of Animal Reproduction, 2021)
A case of dystocia due to vulval stenosis in a crossbred Jersey heifer and its management by episiotomy is reported and described.